2014
DOI: 10.1039/c3fo60395d
|View full text |Cite
|
Sign up to set email alerts
|

The glycemic index of pigmented potatoes is related to their polyphenol content

Abstract: Polyphenol extracts from coloured fruits and vegetables inhibit α-glucosidase in vitro, however it is not known whether this translates into an attenuation of blood glucose response in vivo. We examined this relationship in a GI study by feeding coloured potatoes to 9 healthy volunteers. We also examined the in vitro inhibitory activity of potato anthocyanin extracts on rat intestinal α-glucosidase. Potatoes (Purple Majesty; Red-Y38; Yukon Gold and Snowden) were fed with skin after cooking in a convection oven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Thus, potatoes contain additional constituents that may affect the utilization of starch in the human organism, e.g. varieties rich in polyphenols have been demonstrated to inhibit the catalytic cleavage of starch in the small intestine [58,59], and an inverse association between potato phenol content and GI has been found [60]. Moreover, deep frying is a form of preparation that can significantly increase the fat content of the meal which may consecutively promote the onset of overweight, obesity, and T2D [15,61].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, potatoes contain additional constituents that may affect the utilization of starch in the human organism, e.g. varieties rich in polyphenols have been demonstrated to inhibit the catalytic cleavage of starch in the small intestine [58,59], and an inverse association between potato phenol content and GI has been found [60]. Moreover, deep frying is a form of preparation that can significantly increase the fat content of the meal which may consecutively promote the onset of overweight, obesity, and T2D [15,61].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that natural polyphenols could inhibit pancreatic lipase [ 18 , 57 , 58 ]. Table 1 demonstrates that the inhibitory effects on lipase of S. orientalis extracts correlated well with TPC, TFC, DPPH scavenging activity, reducing power, suppression of dicarbonyl compounds formation, and the inhibition activity on α-glucosidase (R = 0.813–0.985).…”
Section: Resultsmentioning
confidence: 99%
“…α-Glucosidase is an enzyme present in the brush border of the small Li et al UF-LC-DAD-MS n for discovering enzyme inhibitors intestine, whose inhibitors act by a reversible inhibition, could delay the absorption of carbohydrates from the small intestine, and suppress the postprandial blood glucose and insulin levels . Recent studies in the discovery of food and other natural sources of α-glucosidase inhibitors have attracted considerable interest as α-glucosidase is an important biomarker for treating type 2 diabetes mellitus (Li et al, 2009;Ramdath et al, 2014;Tang et al, 2016;Zhou et al, 2012;Zhang et al, 2015). The fruit of hawthorn (Crataegus oxyacantha L.) has been part of foods or confectionaries in different cultures, however hawthorn tree leaves also contained flavonoids that were α-glucosidase inhibitors in a UF-LC-MS n screening study (Li et al, 2009).…”
Section: Screening For α-Glucosidase Inhibitorsmentioning
confidence: 99%
“…(Table 3). These polyphe-nols are commonly found in fruits, vegetables, cereals and pulse grains, thus consumption of these foods are beneficial to blood glucose management Ramdath et al, 2014;Tang et al, 2016;Zhou et al, 2012;Zhang et al, 2015). UF-LC-MS n was used to rapidly and selectively screen and identify major α-glucosidase ligands or inhibitors in Radix Astragali and polyphenols particularly calycosin, formononetin and other isoflavones were found to be strong α-glucosidase inhibitors.…”
Section: Screening For α-Glucosidase Inhibitorsmentioning
confidence: 99%